KARAKTERISTIK TERMAL BRIKET ARANG SEKAM PADI DENGAN VARIASI BAHAN PEREKAT - Patabang, Daud (Jurnal MEKANIKAL, 2012)
The aim of this research is to find out of thermal characteristics of husk briquette with glue materials that is made of tapioca powder with content variations; 7%, 10% and 15%.This research used experiment method to find out of thermal characteristic consists of: High Heating Value HHV, Moisture content M, Ash content A, Volatile Matters content VM, Fixed Carbon Content FC and combustions efficiency. The result of investigations are; HHV = 2789 cal/g, M = 2.67%, A = 39.06 %, VM = 42.92%, FC= 15.53% and combustions efficiency 59.07%. All of them are find out from 7% of glue content materials.